Оцінка і вибір моделі-чемпіона у задачах адаптації моделей прогнозування рівня споживання електроенергії у Smart Grid - Бойко, Ольга Василівна; Комін, Антон Сергійович; Boiko, Olha; Komin, Anton (Запоріжжя : Видавничий дім «Гельветика», 2026)
UA: У статті запропоновано модель оцінки та вибору моделі-чемпіона у задачах адаптації моделей прогнозування рівня споживання електроенергії до умов експлуатації кінцевим споживачем. Модель було перевірено у рамках прототипу інформаційної технології з використанням LSTM-моделі прогнозування. Експеримент проведено на реальних даних про погодинне споживання електроенергії домогосподарством за 8 місяців. У процесі інкрементального навчання було сформовано пул моделей-кандидатів і за допомогою запропонованої моделі на кожному із вікон оцінки було обрано модель-чемпіона з найкращою якістю прогнозів. Це дозволило провести адаптацію моделі прогнозування і покращити RSME на 35.3 % у порівнянні із початковою моделлю, що підтвердило ефективність запропонованої моделі оцінки та вибору моделі-чемпіона. /// EN: The article proposes a model for the evaluation and selection of a champion model in the tasks of adapting electricity consumption forecasting models to the operating conditions of the end consumer. The model applies a multicriteria approach to model evaluation using the RMSE, MAE, WAPE, and Skill metrics. It includes their normalization and combination into a single integral evaluation criterion. Together with the use of a common external evaluation window, this allows forecasting models trained in different time periods to be effectively compared. To reduce the frequency of probable champion model switching, a hysteresis rule was added to the evaluation and selection model. The proposed model was validated in scope of the information technology prototype using an LSTM forecasting model based on the TensorFlow Keras library. The experiment was conducted on real data on the household’s hourly electricity consumption over 8 months. Based on these data, 31 time intervals with a 7-day step were formed, corresponding to a scenario of weekly updates of the forecasting model during its operation. As a result of the incremental training on the specified data intervals, a pool of candidate models was formed, and with the help of the proposed model, a champion model with the best forecasting quality was selected at each of the external evaluation windows. This made it possible to adapt the forecasting model used in the prototype of the information technology and improve its RMSE by 35.3 % compared with the initial version, which confirmed the effectiveness of the proposed model. The obtained results confirm the practical value of the model when deploying HEMS forecasting subsystems for consumers with a small amount of historical data, followed by adaptation to the operating conditions of their network.
Evaluation and champion model selection in the adaptation of electricity consumption forecasting models for Smart Grids
Keywords: периферійні обчислення; машинне навчання; розумні мікромережі; енергоефективність; прогнозування споживання електроенергії; Tensorflow Lite; edge computing; machine learning; microgrids; energy consumption forecasting